2000
DOI: 10.4049/jimmunol.164.8.4393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T Cell Responses to Hev b 3, an Allergen Associated with Latex Allergy in Spina Bifida Patients

Abstract: The prevalence of type I allergy to Hevea brasiliensis latex is particularly high among individuals with frequent exposure such as health care workers and patients with spina bifida (SB). Due to a birth defect of the spinal canal and the resulting neurological and orthopedic defects, these patients require multiple surgeries during childhood. SB patients display a unique pattern of sensitization: IgE-reactivity is preferentially directed against Hev b 3 and Hev b 1, two latex allergens with high sequence simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…exposure of the skin to protein Ags is a highly skewed Th2 response (34,43,44). Likewise, contact-induced responses to protein Ags in humans, including latex hypersensitivity reactions and contact urticaria, also involve Th2 generation (45)(46)(47)(48). Given that the vast majority of children with atopic dermatitis eventually develop some form of allergic airway disease, it is plausible that penetration of environmental allergens through the skin could serve as a major mode of systemic Th2 sensitization in atopic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…exposure of the skin to protein Ags is a highly skewed Th2 response (34,43,44). Likewise, contact-induced responses to protein Ags in humans, including latex hypersensitivity reactions and contact urticaria, also involve Th2 generation (45)(46)(47)(48). Given that the vast majority of children with atopic dermatitis eventually develop some form of allergic airway disease, it is plausible that penetration of environmental allergens through the skin could serve as a major mode of systemic Th2 sensitization in atopic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…T cell responses to several allergens have been characterized thoroughly, indicating that allergen-specific Th2 lymphocytes play a predominant role in these diseases, since cytokines produced by this T cell subset (IL-4, IL-13) are potent IgE-switching factors (1)(2)(3)(4). Specific immunotherapy (SIT) 3 proved to be an efficient treatment for patients suffering from type I allergy to airborne allergens (5).…”
Section: Oligodeoxynucleotides Containing Cpg Motifs Induce Low Levelmentioning
confidence: 99%
“…Bet v 1 and Mal d 1 share approximately 64.5% sequence identity, with the cross-reacting T cell-reactive peptide fragments sharing 50% sequence identity. However, other studies have not demonstrated T cell cross-reactivity between allergens with a similar degree of sequence identity, as was the case for the major latex allergens, Hev b 1 and Hev b 3, despite 47% sequence identity [29]. In light of these studies, and given that single amino acid substitutions can lead to loss of T cell reactivity [30,31,32], it is likely that shared key amino acid motifs are more important for T cell cross-reactivity than whole epitope sequences.…”
Section: Discussionmentioning
confidence: 99%